Early stage valuation : a fair value perspective - Puca, Antonella (Wiley finance series, 2020)
"This book provides a comprehensive and up-to-date overview of the methodologies that are currently being used to value Early Stage Enterprises at fair value for investment, M & A activity and financial reporting. It will reflect the most recent AICPA and IPEV guidance and consider how the recent developments in quantitative modelling (for instance, an expanded use of OPM modelling techniques for ESE valuation) and in the valuation of intangible assets are affecting the valuation of ESEs. It will also reflect the most recent developments in the non-GAAP area, which have been stemming primarily from academic research and from the practice of venture capital investors. The book is meant to be useful for investors and professionals who need tools to make valuation assessments that are coherent with fair value principles, suitable for structuring business transactions, internally consistent and defensible in the face of regulators and investors and that reflect the current trends and latest guidance in this area. The book will include case studies that provide a step-by-step practical application of the guidance"--